2020
DOI: 10.1136/bjophthalmol-2020-316651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of new cases of uveitis at academic and community settings

Abstract: PurposeDescribe the demographics of new patients with uveitis presenting to an urban, academic centre and affiliated, suburban satellite clinics to assess if changes in infrastructure were needed for clinical care. Secondarily, examine the frequency of infectious uveitides.MethodsA retrospective chart review of single academic centre of 436 consecutive, new patients with uveitis (686 eyes) and 3 affiliated, satellite clinics seen by 8 uveitis specialists from 1 July 2013 to 31 March 2017. Demographics recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A prominent feature of our study is the high prevalence of African American patients (67%), which is slightly higher than the percent of African Americans in the Philadelphia population in the 2010 census (41%). 17 Our cohort demonstrated more cases of sarcoidosis compared to previously published studies where the predominant underlying autoimmune disorder was HLA-B27 associated [ 18 , 19 ]. As the incidence of sarcoidosis is higher in African Americans than Caucasians in the United States, and it follows that the patients in our study would have a higher prevalence of sarcoid uveitis [ 20 ].…”
Section: Discussionmentioning
confidence: 67%
“…A prominent feature of our study is the high prevalence of African American patients (67%), which is slightly higher than the percent of African Americans in the Philadelphia population in the 2010 census (41%). 17 Our cohort demonstrated more cases of sarcoidosis compared to previously published studies where the predominant underlying autoimmune disorder was HLA-B27 associated [ 18 , 19 ]. As the incidence of sarcoidosis is higher in African Americans than Caucasians in the United States, and it follows that the patients in our study would have a higher prevalence of sarcoid uveitis [ 20 ].…”
Section: Discussionmentioning
confidence: 67%
“…In academic or tertiary referral settings, there is a higher proportion of patients referred for management of posterior uveitis, panuveitis, or chronic uveitis, due to the nature of these diseases having a higher likelihood of permanent vision loss and requiring IMT. 13,14,15 The need for expertise in academic and tertiary referral settings is supported by our survey demonstrating that over half of respondents practiced in an academic or university setting. A retrospective study using data from the Systemic Immunosuppressive Therapy for Eye Diseases cohort study and the Multicenter Uveitis Steroid Treatment trial found that visual acuity in patients with uveitis have improved visual acuity after initiating care with a uveitis specialist.…”
Section: Discussionmentioning
confidence: 82%